Rubyfruit jungle - Brown, Rita Mae (Bantam, 2015)
A landmark coming-of-age novel that launched the career of one of this country's most distinctive voices. Rita Mae Brown tells the story of Molly Bolt, the adoptive daughter of a dirt-poor Southern couple who boldly forges her own path in America. With her startling beauty and crackling wit, Molly finds that women are drawn to her wherever she goes-- and she refuses to apologize for loving them back.